2002
DOI: 10.1007/s00125-002-0837-2
|View full text |Cite
|
Sign up to set email alerts
|

Permanent diabetes mellitus in the first year of life

Abstract: Aims/hypothesis. The pathogenesis of permanent diabetes mellitus diagnosed early in life is heterogeneous and, in most cases, not known. We aimed at identifying markers differentiating between non-autoimmune and autoimmune diabetes. Methods. The clinical, genetic and epidemiological features of 111 diabetic patients (62 males) who received insulin within 12 months of life were studied. Results. The epidemic curve by age of diabetes onset revealed two subsets of patients at a cutoff of 180 days. In the group wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
1
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 22 publications
6
80
1
7
Order By: Relevance
“…Only those diagnosed in the first 3 months have previously been classified as having neonatal diabetes, and this result confirms that a broader definition is needed when considering KCNJ11 mutations [4]. A cut-off point at 6 months is consistent with previous work looking at autoantibodies and HLA suggesting that type 1 diabetes is rare in those aged below 6 months [22]. Our study would not support testing for KCNJ11 mutations in patients diagnosed after 6 months, although relatives of probands with transient neonatal diabetes have been diagnosed at 3, 5, 22 and 26 years [2,3].…”
Section: Discussionsupporting
confidence: 83%
“…Only those diagnosed in the first 3 months have previously been classified as having neonatal diabetes, and this result confirms that a broader definition is needed when considering KCNJ11 mutations [4]. A cut-off point at 6 months is consistent with previous work looking at autoantibodies and HLA suggesting that type 1 diabetes is rare in those aged below 6 months [22]. Our study would not support testing for KCNJ11 mutations in patients diagnosed after 6 months, although relatives of probands with transient neonatal diabetes have been diagnosed at 3, 5, 22 and 26 years [2,3].…”
Section: Discussionsupporting
confidence: 83%
“…Permanent neonatal diabetes due to homozygous glucokinase mutations (46) or pancreatic aplasia due to homozygous IPF1 mutations (47,48) results in a more severe insulin deficiency as shown by a lower birth weight and a younger age at diagnosis. In keeping with pancreatic autoantibodies being rare in patients who are diagnosed with diabetes before 6 months (45), no patients with Kir6.2 mutations have pancreatic autoantibodies, but these are found in patients with FOXP3 mutations leading to IPEX syndrome (45). Transient neonatal diabetes resulting from the common abnormalities of the imprinted region on 6q24 differs from transient neonatal diabetes caused by Kir6.2 mutations.…”
Section: Kir62 As a Candidate Gene For Neonatal Diabetesmentioning
confidence: 93%
“…A recent Italian study suggested that children diagnosed with diabetes before 6 months of age do not have the genetic characteristics of autoimmune diabetes (15). Many patients from this cohort have since been diagnosed with KCNJ11 mutations (10), but the etiology of diabetes in the remainder is uncertain.…”
mentioning
confidence: 85%